2022
DOI: 10.1177/13678779221094061
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation of foreign memories in domestic political speech: Considerations and effects

Abstract: Within the “politics of memory,” this study conceptually expands understanding of the role of political leaders as active producers of memory. By considering the growing exchangeability of ideas and meanings across cultural and national borders, analysis demonstrates how political leaders adapt and reorient transnational memory narratives’ most iconic events. However, deliberately relying on memories from across the border also embody additional functions that are not entirely focused on the domestic. Identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Foreign past events can thus ‘travel’, albeit by abiding to certain constraints and under certain circumstances (Adams, 2022). While it has been shown that collective memory travels in media and cultural settings, it is not able to do so as freely in political speech.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign past events can thus ‘travel’, albeit by abiding to certain constraints and under certain circumstances (Adams, 2022). While it has been shown that collective memory travels in media and cultural settings, it is not able to do so as freely in political speech.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on its potential for resonance, such diffusion takes place across time—for example the “Battle of Britain” as an argument in favor of the UK leaving the EU—but also across space. References to the French Revolution by those advocating UK independence are a typical example of how foreign memories taken out of context can be instrumentalized in domestic politics (Adams 2022). 2…”
Section: The Making Of Events: the Role Of Historical Narrativesmentioning
confidence: 99%
“…Depending on its potential for resonance, such diffusion takes place across time-for example the "Battle of Britain" as an argument in favor of the UK leaving the EU-but also across space. References to the French Revolution by those advocating UK independence are a typical example of how foreign memories taken out of context can be instrumentalized in domestic politics (Adams 2022). 2 The unfolding of Brexit as a political event shows how different actors can make conflicting political claims by engaging in memory arguments-both courses of action are more clearly exposed in moments of urgency, as actors struggle to interpret their political present.…”
Section: The Making Of Events: the Role Of Historical Narrativesmentioning
confidence: 99%
“…Defined as a social group's beliefs, understandings, and interpretations of the past (Olick, 1999;Olick and Robbins, 1998), collective memory initially concerns constructing consensus (Shils, 1981) and binding people together under a shared (even if invented) narrative (Anderson, 1991). The construction of collective memory is a selective process, influenced by various actors in society (Adams, 2022;Olick and Levy, 1997). Collective memories are altered and reused to reflect and shape reality, define social identity, and create and help to maintain a narrative that will unify the collective (Forde, 2016;Gillis, 1994;Huyssen, 2000).…”
Section: Bonding Narratives and Collective Memoriesmentioning
confidence: 99%